Palladium-catalyzed direct ortho CX bond construction via CH activation of azobenzenes: Synthesis of (E)-1, 2-b(2, 6-dibromo(chloro)-phenyl)diazene. Issue 26 (27th June 2019) - Liu, Qingqing; Luo, Xinxin; Wei, Shujie; Wang, Youzhao; Zhu, Jiaxin; Liu, Yi; Quan, Fenglei; Zhang, Meng; Xia, Chengcai
Graphical abstract: Highlights: Palladium(0)-catalyzed direct C(sp 2 )H halogenation of aromatic azo compounds. The method exhibited a broad substrate scope of azobenzenes. A convenient method syntheses of various ortho -tetrabromo(chloro) azoarenes. Abstract: A palladium-catalyzed direct CX bond formation of azobenzenes with 1, 3-dibromo-5, 5-dimethylhydantoin or trichloro isocyanuric acid via CH activation has been developed. The reaction could proceed smoothly under an air atmosphere at 110 °C in the presence of Pd(Ph3 P)4 in DCE and 13 examples of products were obtained.